Innovative Design and Performance Evaluation of Bionic Imprinting Toothed Wheel - Zhihong Zhang; Xiaoyang Wang; Jin Tong; Carr Stephen (Applied Bionics and Biomechanics)
A highly efficient soil-burrowing dung beetle possesses an intricate outer contour curve on its foreleg end-tooth. This study was carried out based on evidence that this special outer contour curve has the potential of reducing soil penetration resistance and could enhance soil-burrowing efficiency. A toothed wheel is a typical agricultural implement for soil imprinting, to increase its working efficiency; the approach of the bionic geometrical structure was utilized to optimize the innovative shape of imprinting toothed wheel. Characteristics in the dung beetle’s foreleg end-tooth were extracted and studied by the edge detection technique. Then, this special outer contour curve was modeled by a nine-order polynomial function and used for the innovative design of imprinting the tooth’s cutting edge. Both the conventional and bionic teeth were manufactured, and traction tests in a soil bin were conducted. Taking required draft force and volume of imprinted microbasin as the evaluating indexes, operating efficiency and quality of different toothed wheels were compared and investigated. Results indicate that compared with the conventional toothed wheel, a bionic toothed wheel possesses a better forward resistance reduction property against soil and, meanwhile, can enhance the quality of soil imprinting by increasing the volume of the created micro-basin.